Investigation of Doppler Indices in Copper Intrauterine Device-induced Heavy Menstrual Bleeding - Koray Özbay; Fatih Şanlıkan (IMR Press, 2022)
Background: Copper intrauterine devices (IUDs) are one of the most commonly used methods of contraception all over the world. However, nearly 20% of users have their IUD removed due to increased or irregular uterine bleeding. We aimed to investigate if the occurrence of heavy menstrual bleeding (HMB) after application of IUDs could be predicted using transvaginal color Doppler ultrasonography in women without dysmenorrhea. Method: Fifty-five women with regular menstruation without dysmenorrhea who were willing to use an IUD were included in the study. The women were divided into two groups as those whose menstrual characteristics did not change after IUD insertion (group A, n = 31) and those who developed HMB secondary to IUD insertion (group B, n = 24). IUDs were inserted on the 2nd or 3rd day of menstruation in all women and color Doppler assessments of the uterine, arcuate, and utero-ovarian arteries were performed twice; the first measurement was performed just before IUD deployment and the second measurement was performed on the 2nd or 3rd day of menstruation after 2 months. After recording these two measurements, Doppler parameters were compared between the groups. Results: The first and the second pulsatility index (PI) and resistance index (RI) values of the uterine arteries were significantly lower in group B when compared with group A (p < 0.05). Likewise, the first and the second PI values of the arcuate arteries in group B were significantly lower than in group A (p = 0.009 and p = 0.035, respectively). The second RI measurements of the arcuate arteries were significantly lower in group B than in group A (p = 0.037); however, the first RI measurement of the arcuate arteries showed no statistically significant differences between the groups (p = 0.073). The first and the second PI and RI values of the utero-ovarian arteries showed no statistically significant difference between groups A and B. Conclusions: The results propose that low impedance to blood flow in the uterine and arcuate arteries prior to IUD insertion may help predict HMB secondary to IUD insertion in women without dysmenorrhea.